A comprehensive review on natural bioactive films with controlled release characteristics and their applications in foods and pharmaceuticals. (June 2021) - Zhang, Liming; Yu, Dawei; Regenstein, Joe M.; Xia, Wenshui; Dong, Junli
Abstract: Background: A lot of environmental concerns have been caused by the non-degradation of plastic packaging materials. In addition, consumer's preferences for safe, healthy, convenient and high-quality products necessitate the emergence of innovative food packaging systems to maintain the quality of packed food. Sustainable active films provide functionalities that address these demands and provide more protection with a single barrier to the external environment, simultaneously avoiding damage to the environment. Scope and approach: The active agents are blended directly into the film and its active function will be affected by environmental factors and lose its efficacy. Nanoencapsulation techniques can be used for entrapment of active agents to maintain their original characteristics during processing and to improve their physiochemical properties. And it is important to control the release rate of active agents so that they migrate from the packaging material to the product at an appropriate rate. This paper reviews the role of film forming matrices, loading of active agents into biopolymeric nanocarriers, the factors affecting the controlled release properties of active films as well as their underlying mechanisms. The existing applications of active films in the food and pharmaceutical industries are used to prove its application effect. Future trends with active films in the field of material chemistry are also discussed. Key findings and conclusions: Active agents may provide the films with antioxidant and/or antimicrobial properties. The controlled release of biofilms can be achieved by preparing biopolymeric nanocarriers to encapsulate the active agents. Microstructure, molecular interaction and the environment film all affect the controlled release of active film. It has been reported that applications of active films have extended shelf life of perishable products. Active films also offer a large potential in drug delivery. Highlights: Bioactive films have huge prospects in food and pharmaceutical industries. The properties of bioactive films prepared with different matrices are listed. To achieve controlled release, various nanostructure carriers are applied to load active agents. The controlled release factors of bioactive film are introduced from multiple angles. The future trends of natural bioactive films are discussed.